Współpraca sektora publicznego i sektora prywatnego w miejscowościach i regionach turystycznych - Rapacz, Andrzej (Cooperation of Public and Private Sector in Tourist Locations and Regions, 2005)
In the conditions of stronger and more powerful competition referring to, among others, tourist areas (destinations), it has become more important to enter into cooperation with other entities of tourism branch, the due associations and local self-government units. This should lead towards the development of the area attractive and effective promotion at the market. The article emphasizes the necessity of conducting such cooperation, characterizes its participants and the scope of expectations, as well as the advantages resulting from the cooperation for both entities and tourists themselves. Local and regional tourist organizations in Poland become the platform for such cooperation, constituting its form for entities representing private sector (tourist companies active in a given location, region) and public sector (local self-government units and their relationships). The, so far, experiences regarding functioning of such cooperation, which takes the form of mentioned above local and regional tourist organizations' activities, may become the basis for eliminating emerging barriers and for the cooperation intensification.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1074, s. 46-55